How serotonin receptors regulate morphogenic signalling in neurons. (April 2017) - Wirth, Alexander; Holst, Katrin; Ponimaskin, Evgeni
Highlights: Serotonin (5-HT) is critically involved in the regulation of multiple physiological and pathophysiological functions in the CNS. 5-HT operates via a heterogenic receptor family comprising fourteen different receptors in mammals. 5-HT is involved in neural development, neurite outgrowth, somatic morphology, growth cone motility, synapto- and spinogenesis. Evidences raise pivotal roles of 5-HT-mediated morphogenic signalling in mental disorders and neurodegenerative diseases (each bullet point starts in bold writing). Abstract: Serotonin (5-hydroxytrympamine or 5-HT) is one of the phylogenetically oldest neurotransmitters, and the serotonergic system is among the earliest developed neuronal systems. Serotonin is critically involved in regulating multiple physiological functions, acting via a heterogenic receptor family that includes G protein-coupled receptors and ligand-gated ion channels. Although serotonergic neurons comprise a widely distributed and complex network that targets nearly every brain structure, serotonin-mediated signalling is under strict temporal and spatial control. Imbalance in serotonergic signalling is implicated in many pathophysiological conditions, including schizophrenia, Alzheimer's disease, depression, and anxiety. In addition to its well-established role as a neurotransmitter, serotonin is involved in many aspects of neural development, including neurite outgrowth, somatic morphology regulation, growth cone motility, synaptogenesis, and control of dendritic spine shape and density. The morphogenic effects of serotonin are developmentally regulated, and serotonin availability during sensitive developmental stages can modulate the formation and functions of behaviourally relevant neuronal networks in adulthood. Here we provide an overview of the molecular mechanisms responsible for the morphogenic effects of serotonin elicited by its different receptors in neurons. We also discuss the role of serotonin receptor-mediated morphogenic signalling in the development and maintenance of pathophysiological conditions.